ROAD ACCIDENTS IN URBAN AREAS IN ALGERIA. THE CASE OF THE CITIES OF CONSTANTINE AND ALI MENDJELI - Ines Kassah Laouar; Meriem Benmechiche; Maya Ines Benaissa; Laila Bennacer (International Journal of Innovative Technologies in Social Science, 2024)
Road safety is a major concern for countries around the world, as it is directly related to the sense of well-being. Road accidents have serious consequences for the victims and impose considerable economic burdens on the state, since their handling is delicate. The African continent, including Algeria, has a high accident rate. In this study, we chose the state of Constantine because of its national importance. Between 2020 and 2022, it recorded a significant number of accidents, particularly in the new town of Ali Mendjeli and the town of Constantine. These areas, with their dense populations and their high attractiveness due to the diversity of facilities they have, are experiencing very large flows and consequently considerable traffic. A territorial analysis of these accidents allows to highlight the dangerous areas, understand the causes and determine the types of victims. From which the identification of the sites most exposed to accidents has allowed us to identify many factors of this risk.